Closing the Gap : Gender, Transport, and Employment in Mumbai - Alam, Muneeza Mehmood; Cropper, Maureen; Herrera Dappe, Matias; Suri, Palak (World Bank, Washington, DC, 2021)
There is increasing recognition that women experience mobility differently from men. A growing body of literature documents the differences in men and women’s mobility patterns. However, there is limited evidence on the evolution of these mobility patterns over time and the role that transportation networks play in women’s access to economic opportunities. This study attempts to fill these gaps. It contributes to the literature in two ways. First, it documents the differences in men and women’s mobility patterns in Mumbai, India, and the changes in these patterns over time, as the city has developed. Second, it explores whether the lack of access to mass transit limits women’s labor force participation. The study analyzes two household surveys conducted in the Greater Mumbai Region in 2004 and 2019. It finds important differences in the mobility patterns of men and women that reflect differences in the division of labor within the household. These differences in mobility patterns, and their evolution over time, point to an implicit “pink tax” on female mobility. Transport appears to be only one of many barriers to women’s labor force participation and not the most important one.